Policy Strategies for Socialization and Public Education on the Public Service Mall Initiative - Rasiklal, Balkrishna (Journal of Research in Vocational Education, 2025)
The Public Service Mall (MPP) policy in Tasikmalaya City represents an innovative approach to improving the quality and efficiency of public services by integrating various government and non-government services in a single location. Effective socialization and education strategies are crucial to ensuring public awareness, understanding, and utilization of these services. This study explores the key strategies implemented by the Tasikmalaya City Government to disseminate information about the MPP, focusing on communication methods, community engagement, and the use of digital platforms. It also examines the challenges faced in reaching diverse demographic groups and the measures taken to address these obstacles. The findings highlight the importance of a multi-channel approach to maximize outreach, including public campaigns, workshops, social media, and collaboration with local stakeholders. Furthermore, the study underscores the role of education in fostering a culture of service utilization and active participation. This research contributes to understanding how effective socialization and education strategies can support the success and sustainability of public service innovations like the MPP.